Recycled Aggregate Concrete including Various Contents of Metakaolin: Mechanical Behavior - Khaleel H. Younis; Abdulfattah A. Amin; Hemin G. Ahmed; Shelan M. Maruf (Advances in Materials Science and Engineering)
This experimental research investigates the effect of utilizing metakaolin (MK) on the behavior of recycled aggregate concrete (RAC). The RAC incorporates recycled coarse aggregate (RCA) originated from crushing construction and demolition waste. The investigated parameters were RCA and MK contents. Tests of workability and mechanical properties such as compressive strength, splitting tensile strength, flexural strength, and modulus of elasticity were conducted to evaluate the influence of MK on workability and mechanical behavior of RAC. In total, 19 mixes were prepared. These mixes are divided into four groups. Group zero (G0) includes a reference mix containing normal coarse aggregate (NCA) and 3 mixes made with 35%, 70%, and 100% of RCA. Each one of the other three groups (G1, G2, and G3) was made with one content of the three contents of RCA, and each group includes five mixes made with the contents of 4%, 8%, 12%, 16%, and 20% of MK. Empirical models among the mechanical properties of the RAC mixes were developed and compared with models of standard codes of practice such as ACI 318, BS 8110, and Eurocode 2. It was found that MK reduces the workability of the RAC mixes. Nonetheless, the outcomes reveal that MK can improve the compressive, splitting tensile, and flexural strengths and the elastic modulus of RAC. This strength improvement enhances as the content of MK increases. The proposed models for the mechanical properties of RAC made with MK showed good correlations. The developed model for modulus of elasticity is quite close to the Eurocode 2 model, whereas the models of ACI 318 and BS 8110 underestimate the values of the modulus of elasticity.